Implementing root cause analysis in Iranian hospitals: challenges and benefits. (12th January 2016) - Abdi, Zhaleh; Ravaghi, Hamid
Summary: Root cause analysis (RCA) has been widely used for retrospective investigations of patient safety incidents. To increase patient safety competencies, RCA has recently been introduced in Iranian hospitals. The aims of the current study were to explore team members' experiences and perceptions of RCA and to identify the challenges and benefits of using it in Iranian hospitals from their perspective. A qualitative study was conducted consisting of 32 semi‐structured interviews with health professionals who participated in the national training programme and were involved in RCA investigations. Data were analysed using the thematic analysis method. The participants encountered a range of obstacles while conducting RCA, including time constraints, a lack of resources, the blame culture and unsupportive colleagues. They stressed the need for further leadership support and cultural change within the Iranian healthcare system to facilitate the application of RCA. RCA was perceived as a beneficial analytical tool that improved patient care, fostered teamwork and communication among staff and promoted safety culture. This study concluded that applying RCA in the Iranian healthcare setting has had a significant impact on improving commitment to safety. However, the general adoption of this method is hindered by the lack of workplace and system supports. To maximize profits from RCA, clinical leaders must assign a high priority to RCA investigations and support RCA team efforts. Copyright © 2016 John Wiley & Sons, Ltd.